2017
DOI: 10.1109/twc.2017.2655517
|View full text |Cite
|
Sign up to set email alerts
|

Velocity-Aware Handover Management in Two-Tier Cellular Networks

Abstract: While network densification is considered an important solution to cater the ever-increasing capacity demand, its effect on the handover (HO) rate is overlooked. In dense 5G networks, HO delays may neutralize or even negate the gains offered by network densification. Hence, user mobility imposes a nontrivial challenge to harvest capacity gains via network densification. In this paper, we propose a velocity-aware HO management scheme for two-tier downlink cellular network to mitigate the HO effect on the forese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(98 citation statements)
references
References 30 publications
2
96
0
Order By: Relevance
“…Tracking velocity can fundamentally enhance handover algorithm execution by simultaneously decreasing both the handover quantity and the handover delay, as demonstrated in [9,10]. The authors of [9] perceived the effect of the handover execution on communication quality, and they thus proposed a basic, effective, aware handover management scheme endeavoring to maintain longer service continuation with serving base stations (BSs) and decrease the handover rate and its related signaling.…”
Section: Velocity and Handover Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Tracking velocity can fundamentally enhance handover algorithm execution by simultaneously decreasing both the handover quantity and the handover delay, as demonstrated in [9,10]. The authors of [9] perceived the effect of the handover execution on communication quality, and they thus proposed a basic, effective, aware handover management scheme endeavoring to maintain longer service continuation with serving base stations (BSs) and decrease the handover rate and its related signaling.…”
Section: Velocity and Handover Performancementioning
confidence: 99%
“…The authors of [9] perceived the effect of the handover execution on communication quality, and they thus proposed a basic, effective, aware handover management scheme endeavoring to maintain longer service continuation with serving base stations (BSs) and decrease the handover rate and its related signaling. Using mathematical expressions, they demonstrated that the proposed handover method accomplished an impressive gain in terms of throughput.…”
Section: Velocity and Handover Performancementioning
confidence: 99%
“…The total intensity in the DUDe architecture is calculated by the fact that the test user sees the heterogeneous network as a homogenous network with intensity Λ = λ 1 + λ 2 . For the total intensity in the RSS architecture, we exploit the mapping theorem [7,Theorem 2.34] and follow [5,Lemma 3] and map the two dimensional PPPs into an equivalent one dimensional non-homogenous PPP with the resultant intensity…”
Section: Stationary Analysismentioning
confidence: 99%
“…The work in [4] sheds light on the negative impact of mobility on network densification gains in multi-tier cellular networks, in which the concept of Phantom small BSs is utilized to mitigate such negative impact. The work in [5] shows that the RSS based association may impose excessive HOs in dense cellular environments, in which handover skipping is proposed to alleviate unnecessary handovers. However, to the best of the authors' knowledge, the impact of mobility on the uplink association is never addressed in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Thus the HO skips associating to the target MBS if the user trajectory passes through the outer region of its target MBS; that is, when the minimum distance between the user trajectory and its target MBS exceeds the same predefined threshold value D, the HO occurs. However, the high-mobility users will skip HOs to the entire femto tier to avoid the excessive HOs because the FBS coverage area is too small [40]. The high-mobility users will be served directly by their un-skipped MBSs which are their trajectories pass through the inner region of the target MBSs.…”
Section: Location-aware Cross-tier Cooperation Schemementioning
confidence: 99%